The Islamic Law within the ‎Indonesian Legal System ‎(A Case Study of Islamic Sharia Law ‎in Aceh)‎ - Hary Abdul Hakim; Ming Hsi Sung; Chrisna Bagus Edhita Praja; Mutia Qori Dewi Masithoh; Salsabila Rahadatul’ Aisy (Universitas Darussalam Gontor, 2021)
After the peaceful agreement signed by the Indonesian government with the government of Aceh, special autonomy was granted for Aceh and provided additional space for the two governments to improve the relations. Islamic law was fully effected after the assignment of Law No. 22 of 1999 concerning Regional Autonomy and amended by Law No. 11 of 2006 concerning the Law of the Government of Aceh, which provides a legal basis for the Privileges and Application of Islamic Law in Aceh. This research aims at analyzing the history and current existence of Islamic law in Indonesia and its contradiction with human rights. As an effort to enforce Sharia law, the regional government, besides pouring it into regional regulations or what is called Qanun, also forms institutions tasked with ensuring the proper implementation of Islamic Sharia law in Aceh. The research used normative legal research with a statute approach. The data are taken from secondary data. The results found that there were no human rights violations in applying Islamic law in Aceh.